Salvadoran Refugees and Asylum Seekers in Costa Rica: Residential Satisfaction and Intention to Remain - Moya González, José David (2023)
Objective. The objective was to analyze the relationship between residential satisfaction and the intention to remain in Costa Rica among Salvadoran refugees and asylum seekers population, from the San José canton. Method. The sample was based on 41 refugees and asylum seekers; their mean age was 38 years. 33 people were administered a residential satisfaction and intention to remain questionnaire, based on García and Arends (2012), and Aragonés and Corraliza (1992). Finally, 8 people were involved in a focus group. Results. The intention to remain is related to the constant search for security in the neighborhood. The more security one experiences, the greater is the intention to remain. People also seek to improve their neighborhoods, in terms of security, community organization and community protection.